Analisis Aktivitas Komunikasi Pemasaran Digital Megrashy Wedding Planner Dalam Meningkatkan Brand Awareness Melalui Media Sosial Tiktok - Aulia, Mardhatillah; Pamungkas, Indra Novianto Adibayu (eProceedings of Management, 2023)
Advances in technology continue to move rapidly, resulting in various changes in the business sector, with the development of the era of lifestyle and people's needs are also increasing. As a result, people are wiser in choosing the products/services to be used. As a result, digital marketing communication strategies play an important role in business. The digital marketing communication strategy seeks to assist business actors in marketing their products/services digitally using social media, which is believed to be able to help increase Brand Awarenessin order to build a brand and corporate image that sticks in consumers' memories. This research was created to examine Megrashy Wedding Planner's digital marketing communication strategy and the implementation of the use of social media Tiktok in increasing brand awareness. The author uses a qualitative analytical method with an interpretive paradigm. The data validity technique used in this research is source triangulation, namely comparing and verifying the information obtained, theoretical triangulation, which is based on the assumption that facts cannot be verified by one or more theories, and method triangulation, which has two strategies. the first is checking the validation of findings from research results using several data collection techniques, and the second is checking validation from several sources using the same method. Based on the findings of this study, Megrashy Wedding Planner has used Tiktok as a medium for conducting digital marketing to increase brand awareness. The content presented is educative, informative, persuasive about marriage that can be accepted by the audience. This states that Megrashy Wedding Planner has succeeded in using the social media tiktok in increasing Brand Awareness.